Poverty Incidence in Nepal by Caste/Ethnicity: Recent Levels and Trends - Patel, Shambhu Prasad (Academic Voices: A Multidisciplinary Journal, 2013)
Nepal Living Standard Survey (NLSS) 1995/96 is the first survey in Nepal which provides data on poverty by caste and ethnicity. This paper attempts to trace out the levels and trends of poverty in Nepal by caste and ethnicity on the basis of available data. The findings show wide disparity in poverty between and within the social groups. Academic Voices, Vol. 2, No. 1, 2012, Pages 59-62 DOI: http://dx.doi.org/10.3126/av.v2i1.8290